Use of metrics to quantify IMRT and VMAT treatment plan complexity: A systematic review and perspectives. (August 2019) - Antoine, Mikaël; Ralite, Flavien; Soustiel, Charles; Marsac, Thomas; Sargos, Paul; Cugny, Audrey; Caron, Jérôme
Highlights: Plan Complexity Metrics (PCM) are variables that aim to quantify IMRT and VMAT plan complexities. PCM has been published in heterogeneous formalism, this work class and synthetize them. Use of PCM is still institution-dependent. PCM could now be seen as a quality indicator. Abstract: Purpose: Fixed-field intensity modulated radiation therapy (FF-IMRT) or volumetric modulated arc therapy (VMAT) beams complexity is due to fluence fluctuation. Pre-treatment Quality Assurance (PTQA) failure could be linked to it. Several plan complexity metrics (PCM) have been published to quantify this complexity but in a heterogeneous formalism. This review proposes to gather different PCM and to discuss their eventual PTQA failure identifier abilities. Methods and materials: A systematic literature search and outcome extraction from MEDLINE/PubMed (National Center for Biotechnology Information, NCBI) was performed. First, a list and a synthesis of available PCM is made in a homogeneous formalism. Second, main results relying on the link between PCM and PTQA results but also on other uses are listed. Results: A total of 163 studies were identified and n = 19 were selected after inclusion and exclusion criteria application. Difference is made between fluence and degree of freedom (DOF)-based PCM. Results about the PCM potential as PTQA failure identifier are described and synthesized. Others uses are also found in quality, big data, machine learning and audit procedure. Conclusions: A state of the art is made thanks to this homogeneous PCM classification. For now, PCM should be seen as a planning procedure quality indicator although PTQA failure identifier results are mitigated. However limited clinical use seems possible for some cases. Yet, addressing the general PTQA failure prediction case could be possible with the big data or machine learning help.